2017
DOI: 10.1021/acscatal.7b01886
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoxidation inside a C3-Vanadium(V) Bowl-Shaped Catalyst

Abstract: The confined enantiopure oxido-vanadium complex SSS-RRR- 1 was synthesized and tested as a catalyst for the oxidation of sulfides into sulfoxides. This catalyst is very efficient with a reaction rate more than 300 times higher than that of the model compound SSS-RRR- 3, and a turnover number (TON) close to 105 was reached in combination with a good selectivity (more than 90%) in the sulfoxide product. Moreover, enantiomerically enriched sulfoxide can be obtained, breaking through the major limitation of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Supramolecular vanadium complexes have been applied to the selective oxidation of sulfides into sulfoxides [27]. For example, Martinez et al reported in 2017 the synthesis of a novel supramolecular chiral oxidovanadium catalyst 21 that was further investigated as promotor for the sulfoxidation of sulfides [28]. When 40 mol% of this catalyst was applied at 0°C in dichloromethane as a solvent to promote the sulfoxidation of alkyl aryl sulfides 19d,f,j,m-o with tert-butyl hydroperoxide (TBHP) as an oxidant, it afforded the corresponding (R)sulfoxides 20d,f,j,m-o in uniformly excellent yields (93-96%) albeit combined with low enantioselectivities (3-20% ee), as depicted in Scheme 14.…”
Section: Enantioselective Vanadium-catalyzed Sulfoxidationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supramolecular vanadium complexes have been applied to the selective oxidation of sulfides into sulfoxides [27]. For example, Martinez et al reported in 2017 the synthesis of a novel supramolecular chiral oxidovanadium catalyst 21 that was further investigated as promotor for the sulfoxidation of sulfides [28]. When 40 mol% of this catalyst was applied at 0°C in dichloromethane as a solvent to promote the sulfoxidation of alkyl aryl sulfides 19d,f,j,m-o with tert-butyl hydroperoxide (TBHP) as an oxidant, it afforded the corresponding (R)sulfoxides 20d,f,j,m-o in uniformly excellent yields (93-96%) albeit combined with low enantioselectivities (3-20% ee), as depicted in Scheme 14.…”
Section: Enantioselective Vanadium-catalyzed Sulfoxidationsmentioning
confidence: 99%
“…)20d: Ar = Ph, R = Me: 93% yield, 19% ee 20f: Ar = Ph, R = Bn: 96% yield, 19% ee 20j: Ar = p-MeOC 6 H 4 , R = Me: 95% yield, 20% ee 20m: Ar = Ph, R = (1-Naph)CH 2 : 94% yield, 10% ee 20n: Ar = p-NCC 6 H 4 , R = Me: 94% yield, 8% ee 20o: Ar = Ph, R = (9-anthryl)CH 2 : 95% yield, 3% ee 21 Sulfoxidation of alkyl aryl sulfides with TBHP in the presence of supramolecular oxidovanadium catalyst 21[28].…”
mentioning
confidence: 99%
“…However, it should be noted that replacing the northern CTV moiety by a simple phenyl substituent, as in 42 (Scheme 16, b), led to the formation of a bowl-shaped oxidovanadium catalyst capable of catalyzing the direct asymmetric oxidation of thioanisole with 19% ee in an 83% yield. 38 The scope of the synthetic strategy based on resolved Mand P-stereoisomers of CTV(CH 2 CH 2 Br) 3 was also extended to the synthesis of the novel optically pure Mand P-(S,S,S)-43 open structures (Scheme 17). 39 The latter were used as references to unambiguously determine the absolute configuration of four novel open CTV hosts: Mand P-(S,S,S)-43 and Mand P-(R,R,R)-43.…”
Section: -(Sss)-(sss)- M-(sss)-(sss)- P-(sss)-(rrr)and mentioning
confidence: 99%
“…A few regioselective reactions have been reported with this kind of systems where, again, the steric hindrance of the cavity governs the approach of the substrate and therefore the outcome of the reaction. Following the same approach, chiral cavities have been used to induce enantioselective reactions . An example where both enantio‐ and regioselectivities are induced has been reported by Reek for a hydroformylation reaction using an asymmetric container …”
Section: Introductionmentioning
confidence: 99%